Instructional Competencies and Performance Rating of Non-Specialized Teachers Teaching Major Subjects in Senior High Schools - Vicente, Belen (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the extent of instructional competencies and performance ratings of non-specialized teachers teaching major subjects in selected senior high schools in the City Schools Division Office of Antipolo for the School Year 2025–2026. Utilizing a descriptive survey research design and documentary analysis, the study involved eighty (80) non-major teachers from Boso-Boso National High School, Calawis National High School, Canumay National High School, Kaysakat National High School, Maximo Gatlabayan Memorial National High School, Rizza National High School, and San Juan National High School. Respondents were described in terms of age, sex, civil status, educational attainment, position title, length of service, and in-service training participation. A researcher-made questionnaire was used to assess instructional competencies in teaching strategies and pedagogical approaches, classroom management and learning environment, use of assessment and feedback, and professional development. Teachers’ performance ratings were obtained from their Individual Performance Commitment and Review (IPCR).Findings revealed that most respondents were 30 years old and above, female, and pursuing graduate education, with positions ranging from Teacher I to III and with more than five years of service. The respondents demonstrated a very high level of instructional competence across all domains and attained very satisfactory performance ratings. No significant differences were found in instructional competencies based on demographic profile except for in-service trainings attended. Furthermore, teaching strategies and pedagogical approaches were significantly related to performance ratings.The study concluded that continuous professional development enhances instructional competencies, while specialization in teaching assignment influences effectiveness
Keywords: instructional competencies, non-specialized teachers, senior high school, performance rating, pedagogical approaches, teacher performance, professional development